DESIGNING DIGITAL TEACHING MATERIALS FOR TEACHERS AT ELEMENTARY SCHOOL LEVEL - Fitri Senny Hapsari; Miftahul Farid Mochamad Ahyar; Ayi Ahmad Maulana Yusup (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2022)
This public service is intended to help partners at SDN Ratu Jaya 2 Depok increase teachers and students digital literacy. that is a part of a larger movement to make available educational resources designed specifically for use with online education. An approach known as "participatory action research" (PAR) is being used in this study. This endeavor is carried out by the findings of Digital material and digital literacy socialization and workshops; internet-based digital material compilation; internet-based digital material products in education. This investigational process yields digital material (quizizz) that can be implemented in online and offline pedagogy. Second, between the two tests, it is clear that teachers' levels of digital literacy have risen. The study's findings indicate that students can use the final product of digital material creation (quizziz) in their online learning process.